Burn survivors' perception of recovery after injury: A Northwest Regional Burn Model System investigation. Issue 8 (December 2020) - Sibbett, Stephen H.; Carrougher, Gretchen J.; Pham, Tam N.; Mandell, Samuel P.; Arbabi, Saman; Stewart, Barclay T.; Gibran, Nicole S.
Highlights: Physical and psychosocial factors impeded recovery in the first year post-injury. Racial and ethnic minorities reported greater difficulty accessing medical care. Qualitative data provided patient perspectives and supplemented quantitative data. Abstract: Introduction: Previous reports suggest that many factors impact recovery from burn injury. To improve our understanding of these factors, we queried adult burn survivors using a mixed method design during the first year after injury. Methods: An anonymous, 2-page survey was developed and administered to adult burn survivors during routine outpatient clinic follow-up visits at a regional burn center. Participants rated issues of concern and their impacts on return to pre-burn activity levels. Both quantitative and qualitative data were obtained. Descriptive statistics were used to analyze quantitative data and thematic analysis was used to identify, analyze and report patterns from open-ended responses. Results: Over seven months in 2016, 187 patients completed the anonymous survey. Study participants were predominantly male, white, and non-Hispanic. Participants who had not yet returned to pre-burn function reported worse outcomes for all issues queried compared to those who had. Burn survivors from racial and ethnic minority groups reported greater difficulty with accessing medical care and information about their injury as well as higher levels of self-identified posttraumatic stress, issues related to appearance and concerns for loss of strength. Several themes and sub-themes were identified that had both negative and positive impact on early recovery. Such themes included: healing process, psychological recovery and emotional health, and community reintegration/employment. Conclusions: Several themes from responses provided insight into challenges as well as key support systems during the first year of recovery after injury. Collectively, these findings can be used to direct clinical outpatient care, patient education and psychosocial support services.